A 100‐Million‐Year Gap in the Knowledge of the Evolutionary History of Bromeliaceae: A Brief Review of Fossil Records. Issue 1 (20th January 2021) - Kessous, Igor Musauer; Neves, Beatriz; Salgueiro, Fabiano; da Costa, Andrea Ferreira
Abstract : Bromeliaceae arose in the Early Cretaceous, diverging from Typhaceae at ca. 125 Ma. After an apparent evolutionary stasis of 100 million years, they have undergone a high diversification starting in the Miocene. By adding fossils to the phylogenies, one can infer dates of arising and the divergence of lineages and link them to geological and climatic events. The use of reliable fossils, therefore, can greatly impact the results and interpretation of bromeliads evolution. Here, we present a literature review of the fossils assigned to Bromeliaceae and discuss the gap in the knowledge of these plants' evolutionary history in the light of the poor fossil record. Our survey shows that Karatophyllum bromelioides, from the Pleistocene, is the only reliable fossil among the few fossils assigned to the group. Protananaceae has been proposed since 2005 as a sister group of Bromeliaceae; however, no work has corroborated this placement so far. The lack of information in fossil records contributes to the unsolved evolutionary questions between the rise and diversification of the bromeliads. These aspects influence molecular clock calibration and consequently phylogenetic and biogeographical inferences, requiring an alternative calibration. Additional findings may improve our knowledge by revealing new macro/microfossils for Bromeliaceae.